Cerebellar Neurocysticercosis as Long-Term Complication of Allogeneic Haematopoietic Stem Cell Transplantation from Haploidentical Donor - Federico Meconi; Giulia Ciangola; Benedetta Mariotti; Raffaella Cerretti; Laura Cudillo; William Arcese; Alessandra Picardi (Case Reports in Infectious Diseases)
Neurocysticercosis, an infection of the central nervous system with the larval stage of the cestode Taenia solium, is uncommon in developed countries. We report a case of allogeneic haematopoietic stem cell transplantation from a haploidentical donor complicated, in the long term, by T. solium infection of the central nervous system and successfully treated with empiric antiparasitic therapy with albendazole plus dexamethasone. Revised diagnostic criteria proposed by Del Brutto et al. were used for the definitive diagnosis of cerebellar neurocysticercosis.